Implementation of the Balanced Scorecard (Pelaksanaan kad skor berimbang) - Abdullah, Shamsul Nahar; Mohd Yusof @ Mohamed, Borhanudin; Tengku Mohd. Yusof, Tengku Farah Maimunah (Penerbit Universiti Malaysia Terengganu (UMT), 2013)
The balanced scorecard (BSC) was introduced by Kaplan and Norton in 1992 as a result of a comprehensive study over a period of one year involving twelve companies which were deemed to be at the leading edge in performance measurement. Since then, the BSC has been regarded as an important managerial tool that enables a firm to translate its vision and mission into objectives and performance measures which are measurable. Though it has been around for almost two decades, its implementation, especially in Malaysia, is limited. This paper attempts to document a case study of a successful implementation of the BSC involving a Malaysian firm. The results show that company spent a substantial amount of resources to train its staff, create awareness, revisit strategies, and develop scorecards at the company, department and individual levels. To ensure the success of the project, the company formed a BSC steering committee, conducted education programmes and purchase BSC software. It was noted that the BSC assisted employees in clarifying what they should do in relation to the firm's objectives and it helped to align the individual and department effort to the overall corporate mission and vision.